Electromagnetic modelling or artificial pacemaker - Emelia, Gunggu. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Artificial pacemaker is implanted into the body of one whom encounters heart beat failure. It replaces the function of heart pac emaker by controlling heart beat ineffability. The tiny electronic device consists of the lead electrode system, pacemaker itself and connector. The operation of mobile phone produces electromagnetic effects to other electronic devices due to its Radio Frequency (RF). Excessive exposure of electromagnetic (EM) on the artificial pacemaker ma y cause failure to it and discomfort and illness to its user. In order to evaluate the d egree of electromagnetic interference (EMI) on the pacemaker due to EM source such as mob ile phone, it is best to understand the operation of pacemaker and its circuitry. Hence , this research is carried out to develop EM modeling of an artificial heart pacemake r and to determine the radiation impedance, induced by the source voltage and also t he interference voltage and current which exist at the connector of the pacemaker. Simu lated results obtain from programming in Microsoft Visual C++ is used to anal yze the EM modeling of artificial pacemaker when the capacitor of the pacemaker is ch arging and discharging. As the continuous process of charging and discharging of p acemaker’s capacitor will stimulate the heart beat of the user.